Studying Abroad Meets Marginalization: Roma of Greece, Autoethnography, and Academic Tourism - Lagos, Taso G; Singh, Yash; Pace, Andrew; Stone, Erik; Wu, Hongjun; Yan, Hongyi; Forbes-Luong, Shayla (Journal of Tourism Management Research, 2022)
While Greece has historically hosted many minority groups in various relational statuses with the majority population, the Roma uniquely embody practical, psychological and metaphorical spaces that sets them apart from other excluded groups. This study explores the historico-social space that separates the Roma and contextualizes recent developments, including Covid-19, which further marginalizes the group. The transactional space that defines relations between Roma and non-Roma encompasses a ‘gaze’ that disenfranchises Gypsy cultural standing and reduces mutual understanding between mainstream and marginalized communities. This same transactional space is rife with misunderstanding that profits normative day-to-day relations between Roma and those in mainstream society. The paper explores perceptions of the Roma within the Greek social hierarchy, while suggesting study abroad programming, as part of academic tourism, can play a positive role in altering perceptions of minority groups.